Determination of forces in alpine skiing and snowboarding: Validation of a mobile data acquisition system - Stricker, G.; Scheiber, P.; Lindenhofer, E.; Müller, E. (European Journal of Sport Science, 2010)
The aims of this study were (1) to analyse the influence of temperature on the accuracy of a single 3D-dynamometer, (2) to establish the accuracy of a force measurement system that utilizes 3D-dynamometers, and (3) to compare forces measured by pressure insoles and by 3D-dynamometers. Temperature dependence was assessed on a single dynamometer at three different temperatures (23°C, 0°C, -10°C) in a cooling chamber. The relative measurement error was determined in the laboratory with the system mounted on alpine skis and on a snowboard. The forces measured by pressure insoles and by 3D-dynamometers were compared in tests on snow. One skier was used in this part of the study. The average measurement error of a single dynamometer increased from 0.2% to 0.9% when the temperature changed from +23°C to -10°C. At low forces (<292 N), the average measurement error was 4.6% and 3.3% for the ski and snowboard system, respectively. At higher forces (>292 N), the average measurement error decreased to 0.3% and 0.4% for the ski and snowboard system, respectively. The average measurement error for 3D torques ranged from 4.0 to 8.3% for the ski, and from 2.4 to 8.5% for the snowboard system. The deviation of the calculated point of force application from its reference was 1.4 mm (medio-lateral) and 8.8 mm (antero-posterior) for the ski, and 2.7 mm and 10.4 mm for the snowboard system. In general, forces determined by insoles were on average 21% (outer ski) and 54% (inner ski) lower than forces measured by 3D-dynamometers. The similarity in force-time characteristics of the insoles compared with the 3D-dynamometer was high. In conclusion, the temperature had little impact on the measurement accuracy of 3D-dynamometers. The measurement error of 3D-dynamometers decreased with an increase in forces. The accuracy of 3D-dynamometers was similar to that shown in previous studies of measuring systems used in laboratory tests. The 3D-dynamometers increased the standing height by 36 mm and are heavier than insoles, but they provide 3D force and torque data. In skiing and snowboarding, insole measurements are not accurate enough for most biomechanical analyses (e.g. for inverse dynamic calculations). Applications where insole measurements might still be useful could be descriptive analyses of a skiing or snowboarding technique.